Reorientation processes of tilted skyrmion and spiral states in a bulk cubic helimagnet Cu2OSeO3 - Leonov, Andrey O.; Pappas, Catherine (Frontiers in Physics, 2023)
We present a systematic study of tilted spiral states obtained theoretically within the classical Dzyaloshinskii model for magnetic states in cubic noncentrosymmetric ferromagnets. Such tilted spirals are shown to stabilize under competing effect of cubic and exchange anisotropies inherent to cubic helimagnets. By focusing on the internal structure of these spirals and their field-driven behaviour for different aspect ratios of the anisotropy coefficients, we are able to capture the main features of the experimental findings in a bulk cubic helimagnet Cu2OSeO3 and to make a step further towards a complete quantitative model of this chiral magnet. In particular, we show that for strong anisotropy values (which experimentally correspond to low temperatures near zero) there exist an angular separation between the conical and tilted spirals, i.e., the conical spiral flips into a tilted state and immediately composes some finite angle with respect to the field direction. As the anisotropy ratio decreases, such a transition between two spiral states becomes almost continuous and corresponds to higher temperatures at the experiments. In addition, we investigate the field-driven reorientation of metastable skyrmion lattices induced by the competing anisotropies, which may be responsible for some peculiarities at the experimental phase diagrams of Cu2OSeO3.